Strategi Media Promosi yang Efektif sebagai Sarana Publikasi Animasi 2D Sabeni si Pendekar Tanah Abang - Alfons, Jason Armando; Fuad, Ahmad (IAI Nasional Laa Roiba Bogor, 2025)
The story of Sabeni, a martial artist from Tanah Abang, became famous in Betawi after defeating Macan Kemayoran and a Chinese kung fu expert presented by Dutch officials. The reason for choosing this story for a 2D animation is due to its moral message, which teaches the importance of not taking others' rights, helping selflessly, avoiding evil, and remaining determined in facing challenges. Promotional media plays a crucial role in modern marketing strategies, especially in the ever-evolving digital era. This research aims to analyze the effectiveness of various types of promotional media in increasing brand awareness and influencing consumer purchasing decisions. Using both qualitative and quantitative approaches, the study collected data through surveys and in-depth interviews with marketers and consumers. The results indicate that social media, digital advertising, and creative content significantly impact capturing audience attention and building stronger relationships with customers. Additionally, message consistency and appealing design were found to enhance customer loyalty. This research provides valuable insights for marketers in designing more effective and relevant promotional campaigns in today's market. The findings are e xpected to serve as a reference for further research in the field of promotional media and marketing.